Stimulation of Liver Regeneration Using a Titanium Nickelide Implant (Experimental Study) - I. R. Vesir; G. Ts. Dambaev; V. E. Gunter; E. A. Gereng; A. N. Vusik; N. E. Kurtseitov; M. M. Solovev; O. A. Fatushina; E. A. Avdoshina; I. M. Mominov (Acta Biomedica Scientifica, 2020)
Currently, morbidity and mortality from chronic diffuse diseases of the liver and cirrhosis continue to increase worldwide. The difficulty of stabilizing the process with pharmacological agents, lots of restrictions for liver transplantation, the palliative character of the surgical correction of complications determine the urgency of finding various ways to stimulate liver regeneration, including surgical ones. Most of the known methods of surgical stimulation of regeneration are quite traumatic, and their stimulating effect is short-lived. The methods associated with cellular technologies are mostly expensive, ineffective, or poorly understood. In the experimental study, the effect on the parenchyma of a healthy and cirrhotic liver clips for clamping parenchymal organs exerting different unit pressure on the tissue was studied. The object of the study was laboratory rats with a healthy liver and animals with simulated cirrhosis. The animals were operated on with the imposition of titanium nickelide clips on the liver. Changes in the liver were studied 3, 7, 14, and 28 days after the surgery by histological examination of various parts of the liver. It was established that the clip with a lower specific pressure did not cause tissue necrosis, led to atrophy of the marginal part of the liver, also increased hepatocytes and binuclear hepatocytes were observed in the bulk of the liver. A decrease in the proportion of connective tissue was also observed in groups with liver cirrhosis. Thus, we consider it possible to use clips with a certain specific pressure on the tissue as a method of stimulating the reparative properties of the liver in chronic diffuse diseases and cirrhosis of the liver